1991
DOI: 10.1016/0014-5793(91)80508-z
|View full text |Cite
|
Sign up to set email alerts
|

In‐vitro matured human macrophages express Alzheimer's βA4‐amyloid precursor protein indicating synthesis in microglial cells

Abstract: Micr~tllia which are consistenlly associatad with Al~hoimer's disease {AD) );chile plaques ~tre part of the monontJcle:tr phailocyte system, ln.vltro mmured human monocyte.d©rived m;~crophaltcs rc~t,rc many immunological characteristics of microlilia. We found stronll conslJtutive ©xpr0ss~on of' Atxheimcr's//A4.mnyioid precursor protein (APP) in human mononuc|ear pim$ocytes after terminal in.vitro maturation from monoc2ctes to macrophalleS, Amyloid has previously been found to b0 ~s~i.nted wilh microgli~t in A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0
1

Year Published

1992
1992
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(23 citation statements)
references
References 59 publications
5
17
0
1
Order By: Relevance
“…Recent studies demonstrate that overexpression of activated MMP-9 by HEK/APP695 cells promotes the release of APP (80). Many types of cells, including macrophages, express this glycosylated type I integral membrane protein (64). Our MS/MS analysis detected only peptides derived from its ectodomain in medium from M9A macrophages; this is consistent with proteolytic shedding of APP.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Recent studies demonstrate that overexpression of activated MMP-9 by HEK/APP695 cells promotes the release of APP (80). Many types of cells, including macrophages, express this glycosylated type I integral membrane protein (64). Our MS/MS analysis detected only peptides derived from its ectodomain in medium from M9A macrophages; this is consistent with proteolytic shedding of APP.…”
Section: Discussionsupporting
confidence: 68%
“…We selected the ␤ 2 integrin subunit and APP for detailed biochemical characterization because both are transmembrane proteins that have been implicated in human pathology (64,75). ␤ 2 integrin subunit, also termed CD18, is a glycosylated type I membrane protein that is part of a leukocytespecific membrane receptor that is critical for host defense (76).…”
Section: Discussionmentioning
confidence: 99%
“…These datasuggest that both cell types may have the same relationship with the amyloid, e.g., production, secretion, or phagocytosis. While MPS cells are capable of producing P-APP message (Bauer et al, 1991;Haass et al, 19911, this could not be demonstrated for microglia in situ in AD brain (Scott et al, 1993). Alternatively, in AA and AL amyloidoses, MPS cells uptake and process an amyloidogenic precursor and subsequently secrete amyloid fibrils .…”
Section: Basement Membrane Changes In Thementioning
confidence: 91%
“…Of least probability is that microglia play a direct role in the synthesis of amyloid β protein precursor (AβPP) and deposition of Aβ. Although cultured microglia can secrete Aβ and metabolize AβPP in a manner that might favor Aβ deposition [32,39], microglial AβPP mRNA expression is yet to be demonstrated [358]. Conversely, neurons in vivo and neurons in culture exhibit abundant expression of AβPP [213] and are postulated to be the primary source of brain Aβ.…”
Section: Microgliamentioning
confidence: 99%